An Automated Testing Framework for Validating Social Program Management Systems: Bridging Merative Cúram and Legacy Platforms - Sudhakar Mattem, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents an innovative automated testing framework designed to address the challenges of migrating social program management systems from legacy platforms to modern solutions like Merative Cúram. The framework offers a comprehensive approach to system validation, automating the entire testing lifecycle from test case preparation to result comparison and reporting. By leveraging advanced technologies and methodologies, it significantly enhances the accuracy, efficiency, and comprehensiveness of system validation efforts. The article details the framework's technical architecture, including its test case input layer, processing layer, and comparison and reporting layer, as well as its integration with continuous integration and deployment pipelines. Key benefits such as improved accuracy, time and cost efficiency, scalability, and support for continuous testing are discussed. The framework's potential applications in other domains, current limitations, and future research directions are also explored. This article solution represents a significant step forward in ensuring the reliability and consistency of critical social services during complex system migrations, with implications for improving the overall delivery of public services.
Keywords: Automated Testing Framework; Social Program Management Systems; Merative Cúram Migration; Continuous Integration/Continuous Deployment (CI/CD); Legacy System Validation